TV Viewing by Children During Times of Conflict - Millie Ferrer (EDIS)
Amid tragic times of war and terrorism, people naturally want to keep current. However, without realizing it, many families can spend too many hours watching TV. The continuous bombardment of the latest accounts of what is happening in the world can add to children’s fear, confusion, and stress. Experts agree that viewing a lot of violence in the media can be unhealthy for children. Parents need to limit the amount of television coverage their children watch. It is especially important to limit young children’s exposure to graphic images. No matter what age, each person interprets programs and messages differently. Children in particular can easily misinterpret what is going on, thereby increasing their sense of fear. This document is FCS9191, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, IFAS, University of Florida, Gainesville FL 32611.First published: May 2003.